THU0433 Persistency with TNFI in Biologic Experienced versus Biologic Native PSA Patients Enrolled in Corrona Registry. (15th July 2016) - Etzel, C.J.; Stolshek, B.; Rebello, S.; Collier, D.; Mutebi, A.; Wade, S.W.; Malley, W.; Greenberg, J.D.; Harrold, L.R.
Abstract : Background: Little is known about the long-term use of TNFi for the management of PsA in routine clinical practice in the US. Objectives: To assess overall persistence with TNFi and evaluate differences based on patients' prior use or non-use of TNFi in the US Corrona registry. Methods: We identified all PsA initiators of a TNFi (adalimumab, etanercept, infliximab, golimumab) with at least 1 follow-up visit from October 2002 to December 2014. Patients were followed until the earliest of: discontinuation of the TNFi, initiation of another biologic or small molecule therapy or last follow-up visit. Patient characteristics (demographic and clinical characteristics) at the index date (TNFi initiation) were evaluated. Kaplan-Meier curves were used to describe time to discontinuation, with censoring for all patients with a ≥1year gap between office visits. The log rank test was used to assess for differences in persistence (defined as remained on index TNFi) based on prior TNFi use. Results: A total of 1241 patients initiated a TNFi during the study period, with mean (standard deviation [SD]) age and disease duration of 50.7 (12.1) years and 8.3 (8.5) years, respectively. The mean (SD) swollen and tender joint counts were 3.3 (4.8) and 4.7 (6.4). Forty-four percent of patients (n=549) were TNFi-naïve at initiation. Overall, 46% of patients (n=572) discontinued TNFi during follow-up with 83.2%, 66.9%, 52.4%, 40.6% and 36.1% of patients persistent at 6, 12, 24, 36 and 48 months respectively; median time to discontinuation was 27 months (95% CI: 24, 31). Based on the log rank test, persistence was greater in patients on their first TNFi –than in patients with prior TNFi use (Figure ). Conclusions: Over half of all PsA patients included in this study were persistent to TNFi at 24 months post-initiation. TNFi-naïve patients had greater persistence compared to TNFi–experienced patients. Acknowledgement: This study is sponsored by Corrona, LLC. The Corrona RA registry has been supported through contracted subscriptions in the last two years by AbbVie, Amgen, BMS, Crescendo, Genentech, Horizon Pharma USA, Janssen, Eli Lilly, Novartis, Pfizer, and UCB. Disclosure of Interest: C. Etzel Consultant for: Merck, Employee of: Corrona, LLC, B. Stolshek Shareholder of: Amgen, Inc., Employee of: Amgen, Inc., S. Rebello Employee of: Corrona, LLC, D. Collier Shareholder of: Amgen, Inc., Employee of: Amgen, Inc., A. Mutebi Shareholder of: Amgen, Inc., Employee of: Amgen, Inc., S. Wade Consultant for: Amgen, Inc., W. Malley Employee of: Corrona, LLC, Paid instructor for: Lamar University, J. Greenberg Shareholder of: Corrona, LLC, Consultant for: AstraZeneca, Celgene, Genentech, Janssen, Novartis and Pfizer, Employee of: Corrona, LLC, L. Harrold Grant/research support from: Pfizer and Astra Zeneca, Consultant for: Genentech and Pfizer, Employee of: Corrona, LLC